Studies evaluating of health interventions at schools: an integrative literature review - Eliabe Rodrigues de Medeiros; Danielle Gonçalves da Cruz Rebouças; Alany Carla de Sousa Paiva; Camila Priscila Abdias do Nascimento; Sandy Yasmine Bezerra e Silva; Erika Simone Galvão Pinto (Revista Latino-Americana de Enfermagem, 2018)
ABSTRACT Objective: to identify and analyze the available evidence on the strategies used in the studies evaluating health interventions at school. Method: this is an integrative review searching in LILACS, CINAHL, CUIDEN, ScienceDirect, and PubMed. From the pre-defined inclusion and exclusion criteria, there were 121 articles chosen to compose the sample. Results: english studies (97.5%), with a quantitative approach (80.2%), related to the interventions carried out in the Region of the Americas (54.6%) and the European Region (23.1%) predominated. For the most part, they are interventions as programs (70.2%), interested in evaluating results (73.5%) from the value judgment (83.4%). Prevalence of interventions focused on efficacy, effects or impact, and activities carried out on interventions were focused on physical activity, healthy eating, sexual and reproductive health, mental health, and use of tobacco, alcohol, and other drugs. They are worked through activities of clinical monitoring, health promotion and disease prevention. Conclusion: the evidence indicates that the evaluations of health interventions in the school focus the results produced in programs through the judgment of value. The topics most addressed were healthy eating, physical activity, prevention of alcohol and other drugs, among others.